Prime values of a^2+p^4 - Heath-Brown, D; Li, X (Springer, 2016)
Many remarkably difficult conjectures in prime number theory take the form that there are infinitely many primes in some set of natural numbers S . In many interesting examples, we even have conjectured asymptotic formulas for the number of primes in S . Thus, we think that there are infinitely many primes of the form p + 2, a^2 + 1, a^2 + b^6, and so on.